ПОВЫШЕНИЕ ЭФФЕКТИВНОСТИ КРЕМНИЕВЫХ СОЛНЕЧНЫХ ЭЛЕМЕНТОВ - Исмайлов, К.А.; Кенжаев, З.Т.; Яхшимов, С.Г.; Олламберганов, Ш.З. (SCIENCE and SOCIETY, 2021)
It has been shown experimentally that the diffusion of nickel, which is formed by an enriched nickel layer in the near-surface region of silicon, is an effective method for gettering recombination centers in silicon and increases the efficiency of the photocell.
Keywords: silicon; solar cell efficiency; nickel clusters; gettering; lifetime